ER stress induces anabolic resistance in muscle cells through PKB-induced blockade of mTORC1. - Louise Deldicque (Public Library of Science (PLoS), 2011)
Background Anabolic resistance is the inability to increase protein synthesis in response to an increase in amino acids following a meal. One potential mediator of anabolic resistance is endoplasmic reticulum (ER) stress. The purpose of the present study was to test whether ER stress impairs the response to growth factors and leucine in muscle cells. Methods Muscle cells were incubated overnight with tunicamycin or thapsigargin to induce ER stress and the activation of the unfolded protein response, mTORC1 activity at baseline and following insulin and amino acids, as well as amino acid transport were determined. Results ER stress decreased basal phosphorylation of PKB and S6K1 in a dose-dependent manner. In spite of the decrease in basal PKB phosphorylation, insulin (10-50 nM) could still activate both PKB and S6K1. The leucine (2.5-5 mM)-induced phosphorylation of S6K1 on the other hand was repressed by low concentrations of both tunicamycin and thapsigargin. To determine the mechanism underlying this anabolic resistance, several inhibitors of mTORC1 activation were measured. Tunicamycin and thapsigargin did not change the phosphorylation or content of either AMPK or JNK, both increased TRB3 mRNA expression and thapsigargin increased REDD1 mRNA. Tunicamycin and thapsigargin both decreased the basal phosphorylation state of PRAS40. Neither tunicamycin nor thapsigargin prevented phosphorylation of PRAS40 by insulin. However, since PKB is not activated by amino acids, PRAS40 phosphorylation remained low following the addition of leucine. Blocking PKB using a specific inhibitor had the same effect on both PRAS40 and leucine-induced phosphorylation of S6K1. Conclusion ER stress induces anabolic resistance in muscle cells through a PKB/PRAS40-induced blockade of mTORC1.